Antibiotic resistance of clinical isolates of Clostridioides difficile in China and its association with geographical regions and patient age. (December 2019) - Li, Hu; Li, Wen-Ge; Zhang, Wen-Zhu; Yu, Shuan-Bao; Liu, Zheng-Jie; Zhang, Xin; Wu, Yuan; Lu, Jin-Xing
Abstract: It is known that antibiotic usage is associated with the development of Clostridioides difficile infection (CDI), especially clindamycin, third-generation cephalosporins, and fuoroquinolones. Antibiotic resistance rates to many antibiotics varies a lot by study. We performed a study focused on antibiotic resistance in clinical isolates of C. difficile from more widespread geographic regions across China. Of 319 C . difficile isolates tested against 11 antibiotics, 313 (98.1%) were resistant to at least one antibiotic. The highest rate of resistance was to ciprofloxacin, clindamycin, and erythromycin across all age groups, similar to previous studies. However, all isolates were susceptible to metronidazole and vancomycin. Overall the resistance rate to tested antibiotics was lower than other reports in China except for chloramphenicol and meropenem. Genotype ST37/RT017 in clade 4 was resistant to more antibiotics than other types. Unexpectedly, RT078 isolates in this study were susceptible to almost all tested antibiotics. In addition, the proportion of multi-drug resistant (MDR) isolates observed (17%) in this study was much lower than several European studies (up to 55%) and a previous study in China (78%). Although isolates from patients aged between 65 and 85 were more resistant to antibiotics in comparison to other age groups, MDR isolates were still detected in children below 2-years of age. The highest percentage of MDR isolates was determined in South China, an area that is most developed economically. The clade 4, RT017 (ST37) has been associated with outbreaks in Europe and North America and is responsible for most C. difficile infections (CDIs) in Asia. In addition, RT017 is often clindamycin and fluoroquinolone resistant. This study provided a relatively comprehensive description of antibiotic resistance of C . difficile in China, and further elucidates the epidemiology and antibiotic resistance of clinical isolates of C. difficile in China at a national level. Highlights: A total of 319 C. difficile strains were classified into 44 STs/29RTs. Resistances to CIP, CLI and ERY were most common and none was detected for MTZ and VAN. ST37/RT017 in clade 4 showed resistance to more antibiotics than other types. The highest accumulation of resistance was found in RTs 017, 012, 001 and 046. The resistance rates were seem to associated with age and economic developed areas in China.